2013
DOI: 10.1093/icvts/ivt390
|View full text |Cite
|
Sign up to set email alerts
|

Does bicarbonate prevent contrast-induced nephropathy in cardiovascular patients undergoing contrast imaging?: Table 1:

Abstract: A best evidence topic in cardiovascular surgery was written according to a structured protocol. The question addressed was whether administering sodium bicarbonate (NaHCO3) prevents contrast-induced nephropathy (CIN) in cardiovascular patients undergoing contrast imaging. In total, 266 papers were found using the reported search, 16 of which represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…As for hemofiltration, although it was shown to be useful, it was limited by high cost of implementation and impracticality (27). Dabarca et al suggested that SB should be added to treatment hydration with sodium chloride after examining 266 studies including patients with cardiovascular disease who had direct contrasting agent exposure (28). However, in a meta-analysis of 19 studies, Jang et al investigated 3609 patients and asserted that SB was superior to sodium chloride (29).…”
Section: Review Articlementioning
confidence: 99%
“…As for hemofiltration, although it was shown to be useful, it was limited by high cost of implementation and impracticality (27). Dabarca et al suggested that SB should be added to treatment hydration with sodium chloride after examining 266 studies including patients with cardiovascular disease who had direct contrasting agent exposure (28). However, in a meta-analysis of 19 studies, Jang et al investigated 3609 patients and asserted that SB was superior to sodium chloride (29).…”
Section: Review Articlementioning
confidence: 99%
“…Apart from periprocedural hydration, which seems to reduce but not completely prevent the risk of renal injury following radiographic contrast media (RCM) administration ( Jurado-Roman et al., 2015 ; Solomon et al, 1994 ; Eisenberg, Bank & Hedgock, 1981 ), the results of other agents such as dopamine, mannitol, N-acetylcysteine, captoopril and statins are equivocal ( Dabare et al, 2013 ; Weisbord & Palevsky, 2010 ; Verdoodt et al, 2018 ). Since there is no available treatment and even a mild 0.3 mg/dl increase of serum creatinine also associated with a 4.3-fold increase in the odds of death, it is urgent to find the valuable risk factors ( Chertow et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“… 10 Apart from periprocedural hydration, which seems to reduce but not completely prevent the risk of renal injury following RCM administration, 11 13 the results of other agents such as dopamine, mannitol, N-acetylcysteine, and captopril are equivocal. 14 – 20 Statin therapy has also been extensively investigated with some evidence of a protective effect, especially for high-dose statin therapy prior to coronary angiography—particularly in the context of acute coronary syndromes. 21 , 22 However, there is some uncertainty on the impact of statins on renal disease and kidney protection.…”
Section: Introductionmentioning
confidence: 99%